Ramos profile ; Eap's profile ; It's no joke [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Leading presidential candidate and the man most likely to be president talks about his general policy of government. Talks about Erap Estrada's political popularity. Question what kind of senators will showbusiness peopole like Tito Sotto, Freddie Webb and Ramon Revilla be.